Relatório Relativo à Deslocação de uma Delegação da Internacional Socialista à América Latina, de 15 a 25 de Março de 1978
Relatório Relativo à Deslocação de uma Delegação da Internacional Socialista à América Latina, de 15 a 25 de Março de 1978